Taxonomy of Aulacochilus (Coleoptera: Erotylidae: Erotylinae) From China, with a Key Based on Adult Characters - Zhao, Yanchen (J Insect Sci, 2018)
The history of taxonomy of Aulacochilus from China was reviewed. A key based on adult characters to separate the Chinese species of this genus is presented. A map of the collecting sites in China is given. One new species, Aulacochilus xingtaiensis sp. nov., from China is described and illustrated.